The Impact of Lifestyle and External Factors on Male Fertility - Molenda, Marek Jarosław; Woszczyńska, Oliwia Brygida; Rycąbel, Paweł Maciej; Romaniuk, Mateusz; Wachowska, Maria; Paniak, Mateusz; Sowiński, Wojciech Jan; Szymura, Marta; Wojciechowska, Agnieszka Ewelina; Krawczyk , Michał Brunon (Quality in Sport, 2025)
Introduction: In today's world, where expectations for professional success are constantly increasing, modern men are particularly vulnerable to prolonged stress and its negative health consequences. Numerous everyday factors, often overlooked, such as diet, physical activity, and proper recovery, can significantly impact male reproductive capabilities. It is estimated that fertility issues affect approximately 15% of couples worldwide, with male-related factors accounting for about half of these cases. This is a concern that cannot be ignored. This study aims to analyze the influence of lifestyle and various environmental factors on male fertility. Research Objective: The primary aim of this literature review is to evaluate the impact of lifestyle and broadly understood external factors on sperm quality and male fertility in light of the latest scientific research. Materials and Methods: This article is a literature analysis based on publications from the PubMed database between 2014 and 2024, using the following keywords: "stimulants", "male fertility", "physical activity", and "diet." Conclusions: To achieve optimal reproductive function, men should maintain a healthy and balanced diet inspired by the Mediterranean model, along with physical activity tailored to their individual needs. Further research on male fertility is necessary, as current findings do not yet allow for definitive conclusions.